High-strength neodymium iron boron magnetic steel and preparation method

By adding Gd, Cu, Ga and other elements to the NdFeB magnet and adopting a specific process flow, the problems of low strength and machining brittleness of NdFeB magnets are solved, which significantly improves its bending strength and processing toughness, extends the application range and improves yield.

CN119650231APending Publication Date: 2025-03-18NINGBO SONGKE MAGNETIC MATERIAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411629621.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing neodymium iron boron magnet has low strength and is difficult to meet the application needs under conditions such as impact and vibration. In addition, the brittleness leads to serious angle loss during processing, which affects the yield.

Method used

By adding Gd, Cu, Ga and other elements to the NdFeB magnet, adjusting its atomic percentage, and using vacuum smelting, hydrogen crushing, airflow crushing, magnetic field molding, sintering and aging treatment processes, high-strength NdFeB magnets are prepared.

Benefits of technology

It significantly improves the bending strength and processing toughness of neodymium iron boron magnets, reduces defects such as holes, makes the magnets denser, extends the application range of materials, and improves the yield of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650231A_ABST
    Figure CN119650231A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of neodymium-iron-boron magnetic steel, in particular to high-strength neodymium-iron-boron magnetic steel and a preparation method, according to the technical scheme, the high-strength neodymium-iron-boron magnetic steel is composed of RE-M-T-B rare earth compounds and comprises a main phase and a grain boundary phase, RE is selected from one or two or more of La, Ce, Ho, Gd, Pr, Nd, Dy and Tb; m is selected from one or two or more of Al, Cu, Zn, Sn, Ga, Nb, V, W, Ti, Ni, Zr and Mn; t is selected from one or two of Fe and Co; wherein RE is not less than 13.5% and not more than 15.5%, M is not less than 0.6% and not more than 1.2%, and B is not less than 5.5% and not more than 6.4%. According to the neodymium iron boron magnetic steel prepared by the method, the defects such as holes are reduced, the magnet is more compact, the grain boundary phase is well distributed, better toughness is achieved, and the strength and comprehensive performance of the neodymium iron boron magnetic steel are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of NdFeB magnetic steel, and in particular to a high-strength NdFeB magnetic steel and a preparation method thereof. Background Art

[0002] Although sintered NdFeB magnets have excellent magnetic properties, they are brittle materials with poor mechanical properties. In the past, there have been relatively few studies on the mechanical properties of materials, such as the bending strength of materials, machining characteristics, etc. However, with the increasing application of NdFeB magnets in recent years, in some fields, magnets are inevitably subjected to impacts, vibrations, etc., and once the magnets are broken, huge losses will be caused to users. Moreover, during the processing of sintered NdFeB magnets, the brittleness will also cause serious corner nicks in the products, affecting the material yield. In order to increase the application range of materials, meet the potential needs of customers, and improve the qualified rate of material processing, the demand for high-strength NdFeB magnets has gradually increased. Therefore, the present application proposes a high-strength NdFeB magnet and a preparation method. Summary of the invention

[0003] The purpose of the present invention is to provide a high-strength NdFeB magnetic steel and a preparation method thereof in view of the problem that the strength of NdFeB magnetic steel is average in the background technology.

[0004] On the one hand, the present invention provides a high-strength NdFeB magnet, comprising a RE-MTB rare earth compound, including a main phase and a grain boundary phase, wherein: RE is selected from one or two or more of La, Ce, Ho, Gd, Pr, Nd, Dy or Tb; M is selected from one or more of Al, Cu, Zn, Sn, Ga, Nb, V, W, Ti, Ni, Zr, and Mn; T is selected from Fe and / or Co; The atomic percentage content is 13.5%≤RE≤15.5%, 0.6%≤M≤1.2%, and 5.5%≤B≤6.4%.

[0005] Optionally, the RE contains Gd.

[0006] Optionally, M contains Ga and Cu at the same time, and also includes one or two of Ti and Zr.

[0007] Optionally, the RE includes Pr, Nd, and Gd, M includes Cu, Ga, Ti, and Zr, and T includes Fe and Co; Among them, the mass percentage content is 4.6%<Gd / RE<9.8%, Ti+Zr>0.09%, and 0.65%<Cu+Ga<1.0%.

[0008] On the other hand, the present invention provides a method for preparing high-strength NdFeB magnetic steel, comprising the following steps: S1. Melting: The raw materials are vacuum melted in a vacuum medium frequency induction melting furnace at a temperature above 1400°C; then argon is filled in, and centrifugal casting is performed after refining to obtain alloy flakes; S2, hydrogen crushing: placing the alloy flakes in a hydrogen crushing furnace, introducing a mixed gas of argon and hydrogen to make the alloy flakes absorb hydrogen and crush; then heating, dehydrogenation and cooling to obtain hydrogen crushing powder; S3, air flow pulverization: the hydrogen crushed coarse powder is pulverized by an air flow pulverizer under inert gas protection to obtain fine powder with a particle size D50 of 4±0.5μm; S4, pressing and molding: magnetizing the fine powder under a magnetic field to obtain a compact; S5, sintering treatment: sending the compact into a sintering furnace for sintering to obtain a sintered compact; S6. Aging treatment: The sintered blank is subjected to a first aging treatment and a second aging treatment to obtain a NdFeB magnet.

[0009] Optionally, in step S2, the alloy flakes are placed in a hydrogen crushing furnace, and a mixed gas of argon and hydrogen is introduced to allow the alloy flakes to absorb hydrogen and break. The hydrogen absorption time is 2 hours, so that the alloy flakes can fully absorb hydrogen. Then, the alloy flakes are heated while being evacuated. The dehydrogenation time is 5 hours, and the dehydrogenation temperature is 550°C. After sufficient dehydrogenation, the alloy flakes are cooled to obtain hydrogen crushing powder.

[0010] Optionally, in step S3, the jet pressure of the jet mill of the jet mill is 0.6 MPa.

[0011] Optionally, in step S4, the magnetic field strength is 1.8T.

[0012] Optionally, in S5, the sintering furnace temperature is 1075°C, 10 -2 Sintered under vacuum conditions for 6 h.

[0013] Optionally, in step S6, the temperature of the first aging treatment is 850°C-890°C, and the holding time is 4 hours; the temperature of the second aging treatment is 590°C-620°C, and the holding time is 5 hours; the temperature of the third aging treatment is 430°C-480°C, and the holding time is 5 hours.

[0014] Compared with the prior art, the present invention has the following beneficial technical effects: The composite addition of Gd, Cu and Ga in the present invention refines the magnet grains to a certain extent, makes the rare earth-rich phase evenly distributed, reduces defects such as holes, and makes the magnet more compact; NdFeB is a brittle material and is often prone to intergranular fracture at the grain boundary. Gd is added into the main phase of the magnet to replace the atomic position of the rare earth PrNd, making the Nd-rich phase at the magnet grain boundary more abundant, and the bonding force between the grains in the liquid phase contraction process is better, thereby improving the toughness of the product; Cu and Ga have good wettability and processing toughness, and the composite addition of Gd, Cu and Ga can make Cu and Ga well distributed along the grain boundary phase of the magnet, thereby improving the toughness of the product.

[0015] Especially when the mass percentages satisfy 4.6%<Gd / RE<9.8%, Ti+Zr>0.09%, 0.65%<Cu+Ga<1.0%, the processing toughness and bending strength of the magnet are significantly improved, or even doubled. The composite superposition of various effects can obtain ultra-high strength NdFeB magnetic steel products, increase the application range of the material, meet the potential needs of customers, and improve the yield of the material. The NdFeB magnetic steel prepared by the present invention reduces defects such as holes, makes the magnet denser, has a good distribution of grain boundary phase, has better toughness, and improves the strength and comprehensive performance of the NdFeB magnetic steel. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 is a scanning electron microscope image of Example 1; Figure 2 Characterization of Example 1 Figure 1 ; Figure 3 Characterization of Example 1 Figure 2 ; Figure 4 Characterization of Example 1 Figure 3 ; Figure 5 Characterization of Example 1 Figure 4 ; Figure 6 This is a microscopic comparison chart after level 1 aging and level 2 aging. DETAILED DESCRIPTION

[0017] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and specific embodiments.

[0018] A high-strength NdFeB magnetic steel, comprising RE-MTB rare earth compound, including a main phase and a grain boundary phase, wherein: RE is selected from one or two or more of La, Ce, Ho, Gd, Pr, Nd, Dy or Tb; M is selected from one or more of Al, Cu, Zn, Sn, Ga, Nb, V, W, Ti, Ni, Zr, and Mn; T is selected from Fe and / or Co; Among them, the atomic percentage content is 13.5%≤RE≤15.5%, 0.6%≤M≤1.2%, and 5.5%≤B≤6.4%.

[0019] RE contains Gd. M contains Ga and Cu, and also contains one or two of Ti and Zr.

[0020] Further, RE includes Pr, Nd, and Gd, M includes Cu, Ga, Ti, and Zr, and T includes Fe and Co; Mass percentage content, 4.6%<Gd / RE<9.8%, Ti+Zr>0.09%, 0.65%<Cu+Ga<1.0% The following examples are specific implementation steps and test results.

[0021] Embodiment 1: Steps: (1) Melting: The mass ratio of the content of each element in the raw material to the total content is PrNd 30.5wt.%, Gd 1.5wt.%, Cu 0.4wt.%, Ga 0.3wt.%, Co 0.5wt.%, Al 0.4wt.%, Ti 0.15wt.%, Zr 0.1wt.%, B 0.95wt.%, and the balance is Fe; the raw material is vacuum melted in a vacuum medium frequency induction melting furnace above 1400°C; then filled with argon, refined and centrifugally cast to obtain alloy sheets, the average thickness of the alloy sheet is about 0.25mm; (2) Hydrogen crushing: placing the alloy flakes obtained in step (1) in a hydrogen crushing furnace, introducing a mixed gas of argon and hydrogen to allow the alloy flakes to absorb hydrogen and crush; the hydrogen absorption time is 2 hours, so that the alloy flakes can fully absorb hydrogen, and then heating while evacuating the vacuum, the dehydrogenation time is 5 hours, the dehydrogenation temperature is 550°C, and the dehydrogenation is fully carried out. After dehydrogenation, cooling is performed to obtain hydrogen crushing powder; (3) air flow milling: add 0.06% by weight of lubricant to the hydrogen-pulverized powder obtained in step (2), stir and mix under nitrogen protection, and then perform air flow milling. The air flow jet pressure of the air flow mill is 0.6 MPa to obtain fine powder with a particle size D50 of 4±0.5 μm; (4) Pressing and molding: the fine powder obtained in step (3) is pressed and molded in a magnetic field of 1.8 T to obtain a compact; (5) Sintering treatment: The compact obtained in step (4) is sent to a sintering furnace for sintering at 1075°C and 10 ‑2 Sintering was carried out under vacuum conditions of 1000 Pa for 6 hours, and argon gas was filled into the sintering furnace for cooling; (6) Aging treatment: The sintered magnet undergoes the first aging treatment and the second aging treatment; The temperature of the first aging treatment is 875°C, and the holding time is 4 hours; the temperature of the second aging treatment is 620°C; the time of the second aging treatment is 5 hours; the temperature of the third aging treatment is 475°C; the time of the third aging treatment is 5 hours, and a NdFeB magnet with high hardness and good bending strength is obtained.

[0022] (7) After the magnet is machined, a universal testing machine is used to perform a three-point bending strength test to obtain five sets of data.

[0023] Embodiment 2: Steps: (1) Melting: The mass percentage of each element in the raw material is PrNd 30wt.%, Gd 2.0wt.%, Cu 0.4wt.%, Ga 0.3wt.%, Co 0.5wt.%, Al 0.4wt.%, Ti 0.15wt.%, Zr 0.1wt.%, B 0.95wt.%, and the balance is Fe; the raw material is vacuum melted in a vacuum medium frequency induction melting furnace above 1400°C; then filled with argon, refined and centrifugally cast to obtain alloy sheets, the average thickness of the alloy sheet is about 0.25mm; (2) Hydrogen crushing: placing the alloy flakes obtained in step (1) in a hydrogen crushing furnace, introducing a mixed gas of argon and hydrogen to allow the alloy flakes to absorb hydrogen and crush; the hydrogen absorption time is 2 hours, so that the alloy flakes can fully absorb hydrogen, and then heating while evacuating the vacuum, the dehydrogenation time is 5 hours, the dehydrogenation temperature is 550°C, and the dehydrogenation is fully carried out. After dehydrogenation, cooling is performed to obtain hydrogen crushing powder; (3) air flow milling: add 0.06% by weight of lubricant to the hydrogen-pulverized powder obtained in step (2), stir and mix under nitrogen protection, and then perform air flow milling. The air flow jet pressure of the air flow mill is 0.6 MPa to obtain fine powder with a particle size D50 of 4±0.5 μm; (4) Pressing and molding: the fine powder obtained in step (3) is pressed and molded in a magnetic field of 1.8 T to obtain a compact; (5) Sintering treatment: The compact obtained in step (4) is sent to a sintering furnace for sintering at 1075°C and 10 ‑2 Sintering was carried out under vacuum conditions of 1000 Pa for 6 hours, and argon gas was filled into the sintering furnace for cooling; (6) Aging treatment: The sintered magnet undergoes the first aging treatment and the second aging treatment; The temperature of the first aging treatment is 885°C, and the holding time is 4 hours; the temperature of the second aging treatment is 620°C; the time of the second aging treatment is 5 hours, and the temperature of the third aging treatment is 475°C; the time of the third aging treatment is 5 hours, and a NdFeB magnet with high hardness and good bending strength is obtained.

[0024] (7) After the magnet is machined, a universal testing machine is used to perform a three-point bending strength test to obtain five sets of data.

[0025] Embodiment 3: Steps: (1) Melting: The mass percentage of each element in the raw material is PrNd 29wt.%, Gd 3.0wt.%, Cu 0.4wt.%, Ga 0.5wt.%, Co 0.5wt.%, Al 0.3wt.%, Ti 0.15wt.%, B 0.95wt.%, and the balance is Fe; the raw material is vacuum melted in a vacuum medium frequency induction melting furnace above 1400°C; then filled with argon, refined and centrifugally cast into alloy sheets, the average thickness of the alloy sheet is about 0.25mm; (2) Hydrogen crushing: placing the alloy flakes obtained in step (1) in a hydrogen crushing furnace, introducing a mixed gas of argon and hydrogen to allow the alloy flakes to absorb hydrogen and crush; the hydrogen absorption time is 2 hours, so that the alloy flakes can fully absorb hydrogen, and then heating while evacuating the vacuum, the dehydrogenation time is 5 hours, the dehydrogenation temperature is 550°C, and the dehydrogenation is fully carried out. After dehydrogenation, cooling is performed to obtain hydrogen crushing powder; (3) air flow milling: add 0.06% by weight of lubricant to the hydrogen-pulverized powder obtained in step (2), stir and mix under nitrogen protection, and then perform air flow milling. The air flow jet pressure of the air flow mill is 0.6 MPa to obtain fine powder with a particle size D50 of 4±0.5 μm; (4) Pressing and molding: the fine powder obtained in step (3) is pressed and molded in a magnetic field of 1.8 T to obtain a compact; (5) Sintering treatment: The compact obtained in step (4) is sent to a sintering furnace for sintering at 1075°C and 10 ‑2 Sintering was carried out under vacuum conditions of 1000 Pa for 6 hours, and argon gas was filled into the sintering furnace for cooling; (6) Aging treatment: The sintered magnet undergoes the first aging treatment and the second aging treatment; The temperature of the first aging treatment is 880°C, and the holding time is 4 hours; the temperature of the second aging treatment is 620°C; the time of the second aging treatment is 5 hours, and the temperature of the third aging treatment is 440°C; the time of the third aging treatment is 5 hours, and a NdFeB magnet with high hardness and good bending strength is obtained.

[0026] (7) After the magnet is machined, a universal testing machine is used to perform a three-point bending strength test to obtain five sets of data.

[0027] Comparative Example 1 Steps: (1) Melting: The mass percentage of each element in the raw material is PrNd 32wt.%, Cu 0.15wt.%, Ga 0.2wt.%, Co 0.5wt.%, Al 0.4wt.%, Zr 0.2wt.%, B 0.95wt.%, and the balance is Fe; the raw material is vacuum melted in a vacuum medium frequency induction melting furnace above 1400°C; then filled with argon, refined and centrifugally cast into alloy sheets, the average thickness of the alloy sheet is about 0.25mm; (2) Hydrogen crushing: placing the alloy flakes obtained in step (1) in a hydrogen crushing furnace, introducing a mixed gas of argon and hydrogen to allow the alloy flakes to absorb hydrogen and crush; the hydrogen absorption time is 2 hours, so that the alloy flakes can fully absorb hydrogen, and then heating while evacuating the vacuum, the dehydrogenation time is 5 hours, the dehydrogenation temperature is 550°C, and the dehydrogenation is fully carried out. After dehydrogenation, cooling is performed to obtain hydrogen crushing powder; (3) air flow milling: add 0.06% by weight of lubricant to the hydrogen-pulverized powder obtained in step (2), stir and mix under nitrogen protection, and then perform air flow milling. The air flow jet pressure of the air flow mill is 0.6 MPa to obtain fine powder with a particle size D50 of 4±0.5 μm; (4) Pressing and molding: the fine powder obtained in step (3) is pressed and molded in a magnetic field of 1.8 T to obtain a compact; (5) Sintering treatment: The compact obtained in step (4) is sent to a sintering furnace for sintering at 1075°C and 10 ‑2 Sintering was carried out under vacuum conditions of 1000 Pa for 6 hours, and argon gas was filled into the sintering furnace for cooling; (6) Aging treatment: The sintered magnet is subjected to aging treatment; The temperature of the first aging treatment is 900°C and the holding time is 4 hours; the temperature of the second aging treatment is 510°C and the holding time is 5 hours.

[0028] (7) After the magnet is machined, a universal testing machine is used to perform a three-point bending strength test to obtain five sets of data.

[0029] The test data of Examples 1-3 and Comparative Examples are summarized to obtain the following data: Table 1 Test data of Examples 1-3 and Comparative Example 1 The test results show that through the adjustment of the formula, the magnets prepared by the combination of Gd, Ti / Zr, Cu, Ga and other elements, especially when a certain ratio is met, have a significant difference in the bending strength characteristics of the magnets. The element ratio within the appropriate range has good processing toughness and bending strength, and the impact resistance is greatly improved.

[0030] The products prepared in Examples 1-3 and Comparative Example 1 were characterized by scanning electron microscopy. Figure 1-5 , the product prepared in Example 1 was scanned and characterized: refer to Figure 1 It can be concluded that the composite addition of Gd, Cu and Ga, when meeting a certain mass ratio (4.6%<Gd / RE<9.8%, Ti+Zr>0.09%, 0.65%<Cu+Ga<1.0%), can refine the magnet grains to a certain extent, make the rare earth-rich phase evenly distributed, reduce defects such as pores, and make the magnet denser.

[0031] refer to Figure 2-5 It can be concluded that NdFeB is a brittle material and is prone to intergranular fracture at the grain boundary. A certain proportion of Gd is added into the main phase of the magnet (4.6% < Gd / RE < 9.8%) to replace the atomic position of rare earth PrNd, making the Nd-rich phase at the grain boundary of the magnet more abundant, and the bonding force between the grains during the liquid phase contraction process is better, thereby improving the toughness of the product. Among them, Cu and Ga have good wettability and processing toughness (0.65% < Cu+Ga < 1.0%). The composite addition of Gd, Cu, and Ga, when meeting a certain ratio, can make Cu and Ga well distributed along the grain boundary phase of the magnet, effectively improving the toughness of the product.

[0032] refer to Figure 6 , the first aging treatment of Example 1 (temperature of 875°C, holding time of 4 hours) makes the rare earth-rich phase at the grain boundary of the product liquefy and flow between the grain boundaries, the grain boundaries are homogenized, and the main phase grains are well covered; the second aging treatment (temperature of 620°C, holding time of 5 hours), this failure treatment is carried out at the liquid phase change temperature of the CuGa alloy proportion composition, so that the CuGa elements liquefied during the aging and holding process can be evenly distributed in the grain boundaries, playing a good role in grain boundary infiltration. It can be seen that the grain boundary width of the product has increased and gradually become continuous, thereby significantly improving the continuity and structure of the grain boundary. After the present invention optimizes the first two aging treatment processes, the product grain boundary interface is clearer, smoother, and more continuous, the grain refinement effect is good, and the microstructure of the material is successfully optimized, thereby increasing the coercivity, effectively improving the toughness of the product, and improving the mechanical properties of the product.

[0033] The present invention prepares ultra-high-strength NdFeB magnetic steel products, increases the application range of the material, meets the potential needs of customers, and improves the yield of the material.

[0034] The above specific embodiments are only several optional embodiments of the present invention. Based on the technical solutions of the present invention and the relevant inspirations of the above embodiments, those skilled in the art can make various alternative improvements and combinations to the above specific embodiments.

Claims

1. A high-strength NdFeB magnet, characterized in that: It is composed of RE-MTB rare earth compound, including main phase and grain boundary phase, wherein: RE is selected from one or two or more of La, Ce, Ho, Gd, Pr, Nd, Dy or Tb; M is selected from one or more of Al, Cu, Zn, Sn, Ga, Nb, V, W, Ti, Ni, Zr, and Mn; T is selected from Fe and / or Co; The atomic percentage content is 13.5%≤RE≤15.5%, 0.6%≤M≤1.2%, and 5.5%≤B≤6.4%.

2. A high-strength NdFeB magnetic steel according to claim 1, characterized in that: The RE contains Gd.

3. A high-strength NdFeB magnetic steel according to claim 2, characterized in that: The M contains Ga and Cu, and also contains one or two of Ti and Zr.

4. A high-strength NdFeB magnetic steel according to claim 3, characterized in that: The RE includes Pr, Nd, and Gd, M includes Cu, Ga, Ti, and Zr, and T includes Fe and Co; The mass percentage contents are as follows: 4.6%<Gd / RE<9.8%, Ti+Zr>0.09%, 0.65%<Cu+Ga<1.0%.

5. A method for preparing high-strength NdFeB magnetic steel according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Melting: The raw materials are vacuum melted in a vacuum medium frequency induction melting furnace at a temperature above 1400°C; then argon is filled in, and centrifugal casting is performed after refining to obtain alloy flakes; S2, hydrogen crushing: placing the alloy flakes in a hydrogen crushing furnace, introducing a mixed gas of argon and hydrogen to make the alloy flakes absorb hydrogen and crush; then heating, dehydrogenation and cooling to obtain hydrogen crushing powder; S3, air flow pulverization: the hydrogen crushed coarse powder is pulverized by an air flow pulverizer under inert gas protection to obtain fine powder with a particle size D50 of 4±0.5μm; S4, pressing and molding: magnetizing the fine powder under a magnetic field to obtain a compact; S5, sintering treatment: sending the compact into a sintering furnace for sintering to obtain a sintered compact; S6. Aging treatment: The sintered blank is subjected to a first aging treatment, a second aging treatment and a third aging treatment to obtain a NdFeB magnet.

6. The method for preparing high-strength NdFeB magnetic steel according to claim 5, characterized in that: In the step S2, the alloy flakes are placed in a hydrogen crushing furnace, and a mixed gas of argon and hydrogen is introduced to make the alloy flakes absorb hydrogen and break. The hydrogen absorption time is 2 hours, so that the alloy flakes can fully absorb hydrogen. Then, the alloy flakes are heated while being evacuated. The dehydrogenation time is 5 hours, and the dehydrogenation temperature is 550°C. After dehydrogenation, the alloy flakes are cooled to obtain hydrogen crushing powder.

7. The method for preparing high-strength NdFeB magnetic steel according to claim 5, characterized in that: In the step S3, the jet pressure of the jet mill of the jet mill is 0.6 MPa.

8. The method for preparing high-strength NdFeB magnetic steel according to claim 5, characterized in that: In step S4, the magnetic field strength is 1.8T.

9. The method for preparing high-strength NdFeB magnetic steel according to claim 5, characterized in that: In S5, the sintering furnace temperature is 1075°C, 10 -2 Sintered under vacuum conditions for 6 h.

10. The method for preparing high-strength NdFeB magnetic steel according to claim 5, characterized in that: In step S6, the temperature of the first aging treatment is 850°C-890°C, and the holding time is 4 hours; the temperature of the second aging treatment is 590°C-620°C, and the holding time is 5 hours; the temperature of the third aging treatment is 430°C-480°C, and the holding time is 5 hours.